Trends in use of echocardiography in hospitalized patients with syncope. Issue 1 (26th November 2018) - Satish, Mohan; Walters, Ryan W.; Alla, Venkata Mahesh
Abstract : Purpose: We sought to assess the trends in use, predictors of echocardiography, and its impact on in‐hospital mortality in patients admitted with syncope using a large national database. Methods: Utilizing the Nationwide Inpatient Sample (NIS) database from 2001 to 2014, we identified adult patients (>18 years) with a primary discharge diagnosis of syncope and use of echocardiogram was ascertained. Results: A total of 3 174 619 patients with a primary discharge diagnosis of syncope were identified, of which 184 167 (5.8%) underwent an echocardiogram. The rate of syncope hospitalization remained constant between 2001 and 2009 (1.1/1000 US population) but has since decreased steadily to about 0.5/1000 US population in 2014. After adjusting for patient and hospital characteristics, the rate of echocardiogram use increased significantly from 5.1% in 2001 to 6.8% in 2014 (2.7% relative increase per year [ P trend = 0.024]). Predictors of use were cardiac disorders, hypertension, diabetes, peripheral vascular disease, and renal failure. After adjusting for baseline risk, use of echocardiography was not associated with in‐hospital mortality (OR = 0.827, P = 0.155), but was associated with a 14.6% increase in adjusted length of stay and a 22.6% increase in adjusted hospital cost compared to no echocardiography use (both P < 0.001). Conclusions: The admission rates for syncope are decreasing and use of echocardiography in hospitalized patients with syncope is appropriately low. Given the lack of any favorable impact on mortality and the association with increased costs, there is a continued need to emphasize evidence‐based use of echocardiography in patients presenting with syncope.